Optimalisasi Penggunaan Mobile Banking Syariah Bagi Nasabah : Analisis Jaringan Untuk Meningkatkan Efisiensi - Yusnidar Yusnidar; Sofiana Zahara Lubis; Nurbaiti Nurbaiti (Pusat Riset dan Inovasi Nasional, 2024)
This research explores the optimization of network utilization to enhance the efficiency of Shariah Mobile Banking services for customers. The study delves into the theoretical framework of Shariah Mobile Banking, elucidating its customer benefits, technology, and the role of networks. Employing a qualitative research approach, the study aims to examine the efficiency of Shariah Mobile Banking services. The findings underscore the paramount importance of efficiency in Shariah Mobile Banking and highlight the pivotal role of network concepts in augmenting this efficiency. The discussion also identifies hurdles encountered in optimizing Shariah Mobile Banking services and proposes viable solutions to overcome these challenges. This research contributes valuable insights for financial institutions and providers of Shariah Mobile Banking services to improve their service efficiency through network optimization. Additionally, it broadens the understanding of the customer benefits derived from Shariah Mobile Banking. The outcomes are anticipated to inform strategies and actions aimed at enhancing the overall user experience of Shariah Mobile Banking for customers.